Risk of surgical site infection in paediatric herniotomies without any prophylactic antibiotics: A preliminary experience - Dhananjay Vaze; Ram Samujh; Katragadda Lakshmi Narasimha Rao (Wolters Kluwer Medknow Publications, 2014)
Background: Different studies underline the use of pre-operative antibiotic prophylaxis in clean surgeries like herniotomy and inguinal orchiopexy. But, the meta-analyses do not recommend nor discard the use of prophylactic pre-operative antibiotics. The scarcity of controlled clinical trials in paediatric population further vitiates the matter. This study assessed the difference in the rate of early post-operative wound infection cases in children who received single dose of pre-operative antibiotics and children who did not receive antibiotics after inguinal herniotomy and orchiopexy. Materials and Methods: This randomised prospective study was conducted in Paediatric Surgery department of PGIMER Chandigarh. Out of 251 patients, 112 patients were randomised to the case group and 139 were ascribed to the control group. The patients in control group were given a standard regimen of single dose of intravenous antibiotic at the time of induction followed by 3-4 days of oral antibiotic. Case group patients underwent the surgical procedure in similar manner with no antibiotic either at the time of induction or post-operatively. Results: The incidence of surgical site infection in case group was 3.73 % and that in control group was 2.22%. The observed difference in the incidence of surgical site infection was statistically insignificant (P value = 0.7027). The overall infection rate in case and control group was 2.89%. Conclusions: Our preliminary experience suggests that there is no statistically significant difference in the proportion of early post-operative wound infection between the patients who received single dose of pre-operative antibiotics and the patients who received no antibiotics after inguinal herniotomy and orchiopexy. The risk of surgical site infection in paediatric heriotomies does not increase even if the child's weight is less than his/her expected weight for age.